Royal Courts in Dynastic States and Empires : a global perspective - Duindam, Jeroen (2011)
"In recent decades the history of premodern states and empires has undergone major revision. At the heart of this process stood the court, encompassing the household as well as government institutions. This volume for the first time brings together the fruits of research on royal courts from antiquity to the modern world, from Asia to Europe. The authors are acknowledged specialists in their own fields, but they address themes relevant for all courts: the inner and outer dimensions of court architecture as well as staff organizations; the connections between court, capital, and realm; the relationship of the ruler with relatives and other elites. This volume pioneers comparative history combining a rich empirical orientation with a critical assessment of theoretical perspectives. Contributors: Tülay Artan, Gojko Barjamovic, Peter Fibiger Bang, Jeroen Duindam, Sabine Dabringhaus, Nadia Maria El Cheikh, Ebba Koch, Metin Kunt, Paul Magdalino, Rosamond McKitterick, Ruth Macrides, Rolf Strootman, Isenbike Togan, Maria Antonietta Visceglia, and Andrew Wallace-Hadrill."